Sikap Dengan Perilaku Pekerja Seks Komersial (Psk) Tentang Pencegahan Infeksi Menular Seksual (Ims) - Claudia Raynera; Sri Wahyuni; Sri Sumarni (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2013)
Background: There are 26 Public Health Centers in the district of Semarang. The PHC of Bergas is the highest number of sexually transmitted infection cases. There are 767 cases which is occurred during 2012 at Tegalrejo Bergas Localization.The problem in this study is “is there any relationship between the attitude with prevention behaviors about Sexually Transmitted Infections by sexual commercial workers in brothels Tegalrejo, Bergas, Semarang in 2013.Method: This research is quantitative research. The design in this study is used a correlation study and using cross-sectional approach. The variables of this study is the attitude and behavior about prevention behaviors about Sexually Transmitted Infections of sexual commercial workers. The subjects were commercial sex workers who working at Localization of Tegalrejo, Bergas, Semarang. There are 150 populations. However, only 60 respondents were involving in this study. The simple random sampling is used in this study. The data was gained by quessionaires. Moreover, the data was analized by frequency distribution and chi square analysis.Result: The results showed that there were 56.7 % of respondens at health reproductive age. The highest number of level education was 56.7 % who have a basic education level. Moreover, most of respondens have positive attitude (56.7 %) about prevention in Sexually Transmitted Infections. The positive behaviors was 61.7 %, more than the number of responden who did negative behaviour about prevention in Sexually Transmitted Infections.Conclusion: It is concluded that there is a relationship between the attitude with prevention behaviors about Sexually Transmitted Infections by sexual commercial workers in brothels Tegalrejo, Bergas, semarang which was showed by ρ value 0.001. It is expected to health care professionals in order to improve the programs are closely to do intensive counseling and distributing more condoms for sexual commercial workers, who has a high risk of sexually transmitted infections.Keywords: attitudes, behaviors, sexually transmitted infections